Promoting Use of Urban Kitchen Gardens to Alleviate Food Insecurity in Embu Town - Njiraini, Risper Nyakio (University of Embu, 2017)
Use of urban kitchen gardens have been on the rise among some urban households. Their use has been promoted to curb the food insecurity in the urban areas. The use of kitchen gardens is rising especially in the urban areas due to the rise in urbanization and the continued need to meet the daily nutrient requirement among urban households. There is also the need for households to have supply healthy nutritious vegetables that are high in nutrient content that are free from chemical residues. The current research was carried out in Majengo ward in Embu town to determine the popularity of kitchen gardening among urban households. The study involved forty urban household members who gave their feedback in the questionnaire (Appendix 1). Random sampling of the households was used to determine the respondents and to avoid bias. The information collected was keyed in and analyzed using IBM SPSS software 16.0. The results revealed that kitchen gardening is popular among urban households in Majengo ward. Crops grown on the kitchen gardens include kales, onions, and indigenous vegetables such as Amaranth and fruit trees such as tree tomato. The urban households cited challenges such as insufficient water, inadequate space and insect pests and diseases attacking crops on the kitchen garden. This study concludes that urban families can use hanging gardens and containers to grow vegetables in their balconies due to the limited space available for growing vegetables. It is recommended that extension agents could provide information to urban farmers on good agricultural practices in management of insect pests and diseases.